On Asymptotic Behaviour of Solutions to n-Dimensional Systems of Neutral Differential Equations - H. Šamajová; E. Špániková (Abstract and Applied Analysis)
This paper presents the properties and behaviour of solutions to a class of n-dimensional functional differential systems of neutral type. Sufficient conditions for solutions to be either oscillatory, or limt→∞yi(t) = 0, or limt→∞|yi(t)|=∞, i=1,2,…,n, are established. One example is given.